2001
DOI: 10.1155/s1064744901000394
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Clindamycin on Lactobacillus in vitro

Abstract: Objective: To evaluate the in vitro effect of varying concentrations of clindamycin on Lactobacillus spp. Methods: Concentrations of clindamycin ranging from 1.95-20 000 mg/ml were studied for their effect on the growth of six strains of Lactobacillus. Results: Clindamycin concentrations between 1.95-31.25 mg/ml had no statistically significant effect on growth of lactobacilli (p > 0.05). Concentrations 125 and 250 mg/ml had a bacteriostatic effect. The mean minimum inhibitory concentration (MIC) for studied L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…7 One limitation of this study is that we did not obtain vaginal swabs for assessment of the vaginal flora after treatment with clindamycin and before administration of lactobacilli. Based on results reported by Aroutcheva et al, 28 clindamycin most likely had the same effect in both study groups, not only eliminating pathogenic microorganisms but also lowering the number of lactobacilli. Therefore, the vaginal flora in the intervention group after antibiotic treatment and before administration of lactobacilli is likely to have been similar to that in the control group.…”
Section: Discussionmentioning
confidence: 57%
“…7 One limitation of this study is that we did not obtain vaginal swabs for assessment of the vaginal flora after treatment with clindamycin and before administration of lactobacilli. Based on results reported by Aroutcheva et al, 28 clindamycin most likely had the same effect in both study groups, not only eliminating pathogenic microorganisms but also lowering the number of lactobacilli. Therefore, the vaginal flora in the intervention group after antibiotic treatment and before administration of lactobacilli is likely to have been similar to that in the control group.…”
Section: Discussionmentioning
confidence: 57%
“…during the week following therapy with metronidazole but not clindamycin is expected, since clindamycin has a broad spectrum of activity against anaerobic as well as aerobic and facultative organisms, like Lactobacillus spp. (2). Metronidazole is a nitroimidazole with activity against obligately anaerobic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that the coprisin analogue exerts antibiotic activity against C. difficile but not against the gastrointestinal tract-resident organisms Lactobacillus and Bifidobacterium. Notably, clindamycin has antibiotic activity against both nor-mal microbiota (5) and C. difficile (17); this nonselectivity may be a main cause for antibiotic-associated diarrhea and pseudomembranous colitis in both animals and humans.…”
mentioning
confidence: 99%